2008
DOI: 10.53841/bpsfpid.2008.6.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the HoNOS-LD: Further evidence of its validity and use as a generic outcome measure

Abstract: The HoNOS-LD seems reliable and sensitve to change when used as a team generic outcomes measure. In this paper we examine the factor structure of HoNOS-LDs administered at the end of assessment and prior to intervention (N=155). Four hypothesised factors were proposed as externalising behaviour problems, internalising behaviour problems, loss of skills, and loss of community presence. Factor analysis with Varimax rotation yielded four sizaeble factors accounting for 48 per cent of the variance. However, the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…2018) or as five separate ratings, resulting in the measure being reported as having 22 items (e.g. Skelly and D'Antonio 2008; Turton, 2020). Harris et al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2018) or as five separate ratings, resulting in the measure being reported as having 22 items (e.g. Skelly and D'Antonio 2008; Turton, 2020). Harris et al .…”
Section: Methodsmentioning
confidence: 99%
“…Tenneij et al 2009;Esteba-Castillo et al 2018) or as five separate ratings, resulting in the measure being reported as having 22 items (e.g. Skelly and D'Antonio 2008;Turton, 2020). Harris et al (2018) described a systematic review of the HoNOS family of measure and proposes a seven-factor structure that incorporates a single rating for item 3.…”
Section: Honos-ldmentioning
confidence: 99%
See 1 more Smart Citation